Historical and Institutional Determinants of Universities’ Role in Fostering Entrepreneurship - Chepurenko, Alexander; Kristalova, Maria; Wyrwich Michael (Foresight and STI Governance, 2019)
Institutions play a key role in building entrepreneurial ecosystems (EEs). However, the academic literature does not well represent the historical roots of these institutions and most works are devoted to developed countries. This article examines the institutional conditions for the development of scientific and entrepreneurial activities at universities in the context of the transition to a market economy. It considers the «path dependence» (mentality and infrastructure inherited from the past), as well as specific mechanisms for regulating the interaction of universities and other subjects of EE developed during the transition period. Such an approach allows us to assess the potential of universities for the development of entrepreneurship in countries with a transition economy and the impact of historical development paths upon the current structural conditions and the specific features of the EE.